Giant adrenal tumor presenting as Cushing's syndrome and pheochromocytoma: A case report - Puskal Kumar Bagchi; Somor Jyoti Bora; Sasanka Kumar Barua; Rajeev Thekumpadam Puthenveetil (Asian Journal of Urology)
We report a case of a 35-year-old lady who presented with Cushingoid features and associated raised urinary metanephrine. The patient underwent open adrenelectomy. Histopathological examination revealed adreno-cortical carcinoma with microscopic lymphovascular invasion. Postoperative period was uneventful and is on follow-up for the last one year and is doing well.